1996
DOI: 10.1021/bi9524777
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Surface Hydrophobic Residues in the Interfacial Catalysis of Bovine Pancreatic Phospholipase A2

Abstract: The interfacial binding is a unique and important step in the phospholipase A2 (PLA2) catalyzed hydrolysis of phospholipids which is distinct from the binding of a substrate to the active site. To assess the roles of surface hydrophobic residues of PLA2 in these processes, we selectively mutated Leu-19 and Leu-20 of bovine pancreatic PLA2 to charged (L19K and L20K), uncharged polar (L19S and L20S), and amphiphilic (L19W and L20W) groups and measured their kinetic and binding properties using various phospholip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 33 publications
5
38
0
Order By: Relevance
“…Differential Roles of C1 and C2 Domains in Membrane Binding of PKC-␣-For most peripheral membrane binding proteins, both electrostatic and hydrophobic interactions play roles in their membrane binding, although their relative contributions vary with the type of proteins (17,41,42). We have shown that the membrane binding of PKC-␣ is also driven by these interactions; electrostatic interactions of the protein-bound calcium ions and other cationic residues of PKC-␣ with anionic phospholipids and hydrophobic interactions resulting from the Ca 2ϩ -and PS-dependent penetration of PKC into the hydrophobic core of the membrane (4, 12).…”
Section: Discussionmentioning
confidence: 99%
“…Differential Roles of C1 and C2 Domains in Membrane Binding of PKC-␣-For most peripheral membrane binding proteins, both electrostatic and hydrophobic interactions play roles in their membrane binding, although their relative contributions vary with the type of proteins (17,41,42). We have shown that the membrane binding of PKC-␣ is also driven by these interactions; electrostatic interactions of the protein-bound calcium ions and other cationic residues of PKC-␣ with anionic phospholipids and hydrophobic interactions resulting from the Ca 2ϩ -and PS-dependent penetration of PKC into the hydrophobic core of the membrane (4, 12).…”
Section: Discussionmentioning
confidence: 99%
“…Monolayer Measurements-The penetration of PH domains into the phospholipid monolayers of different lipid compositions was measured in terms of the change in surface pressure () using a 10-ml circular Teflon trough and a Wilhelmy plate connected to a Cahn microbalance as described previously (40,(43)(44)(45)(46).…”
Section: Methodsmentioning
confidence: 99%
“…Mutants of human group IIA [41] and pancreatic group I PLA # s [42][43][44] have also shown the importance of tryptophan residues on the IBS for enhanced binding to both neutral and anionic vesicles. Of the AtxA Phe#% mutants studied in the present paper, F24W shows the highest enzymic activity, close to that of the wild type.…”
Section: Figure 2 Inhibition Of Cross-linking Of 125 I-atxc With the mentioning
confidence: 99%